2017
DOI: 10.1103/physreva.95.043819
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced entanglement of two different mechanical resonators via coherent feedback

Abstract: It was shown [New J. Phys. 17, 103037 (2015)] that large and robust entanglement between two different mechanical resonators could be achieved, either dynamically or in the steady state, in an optomechanical system in which the two mechanical resonators are coupled to a single cavity mode driven by a suitably chosen two-tone field. An important limitation of the scheme is that the cavity decay rate must be much smaller than the two mechanical frequencies and their difference. Here we show that the entanglement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 98 publications
1
76
0
Order By: Relevance
“…Here, we demonstrate for the first time this method, by accurately measuring the mean energy of a nanocantilever in thermal equilibrium at millikelvin temperatures. We infer an experimental upper bound on λ, which is 2 orders of magnitude stronger than that set by matter-wave interferometry [20][21][22] for r C ¼ 10 −7 m, and the strongest one to date for r C > 10 −6 m. Theoretical model.-The detection of CSL-induced heating in realistic optomechanical systems has been extensively discussed in the recent literature [15][16][17][18][19]. Here we summarize the main steps.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we demonstrate for the first time this method, by accurately measuring the mean energy of a nanocantilever in thermal equilibrium at millikelvin temperatures. We infer an experimental upper bound on λ, which is 2 orders of magnitude stronger than that set by matter-wave interferometry [20][21][22] for r C ¼ 10 −7 m, and the strongest one to date for r C > 10 −6 m. Theoretical model.-The detection of CSL-induced heating in realistic optomechanical systems has been extensively discussed in the recent literature [15][16][17][18][19]. Here we summarize the main steps.…”
mentioning
confidence: 99%
“…11AE2 times larger at r C ¼ 10 −6 m. The direct effect of collapse models like CSL is to destroy quantum superpositions, resulting in a loss of coherence in interferometric tests with matter-wave [6][7][8] or mechanical resonators [9][10][11]. Recently, noninterferometric tests have been proposed, which promise to set stronger bounds on these models [12][13][14][15][16][17][18][19]. Among such tests, the measurement of heating effects in mechanical systems, a byproduct of the collapse process, seems particularly promising [15][16][17][18].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, various theoretical analyses of multiple resonators coupled to radiation pressure have been put forward [41][42][43][44][45][46][47][48][49][50][51][52]. In particular, a recent proposal showed that arbitrary graph states may be generated in an array of resonators immersed in a cavity field [53] using a generalisation of the reservoir engineering sometimes used for cooling [19,21,37,54].…”
Section: Introductionmentioning
confidence: 99%